The Use of Clustering Technique to Improve Students’ Writing Skill in Descriptive Text (A Case of The Seventh Grade Students of SMP Negeri 1 Kragan Rembang) - Isrinda Krisna Armytasari (Wawasan Pendidikan, 2023)
AbstractThis research focuses on improving writing skills in descriptive text using clustering technique. Writing skill is one of the skills that are quite complicated to learn because it requires extra thought to produce words, phrases, sentences, and even paragraphs in a text. Many students still find difficult to explore and develop their idea, students write content not related to the topic, and students write ideas and sentences are not organized well. The sample was students of the seventh-grade of SMP Negeri 1 Kragan Rembang with total was 64 students. The researcher uses experimental research. There were two groups namely experimental group consist of 32 students and control group consist of 32 students. Instrument of the research was writing test. The researcher conducted pre-test and post-test sessions. Data collection was done by using quantitative method. Based on data analysis from the experimental group showed that the mean of pre-test was 58.84 while post-test was 72.84. In the control group showed that the mean of pre-test was 60.59 while post-test was 68.13. In the T-test showed that the sig. (2-tailed) of experiment and control group were 0.000 <0.05. It means that there is a significance difference in the result of students' learning scores between experiment and control group. The result of this research showed that clustering technique can improve students’ writing skill in descriptive text. Clustering technique is a good and easy technique to help develop and organize ideas in writing.